Önkormányzati gazdálkodás és a területfejlesztés az Északnyugat-Dunántúlon - Lados, Mihály (Tér és Társadalom, 1997)
The essay attempts to assess what resources the governments of Northwest Transdanubia – i.e. Győr-Moson-Sopron, Vas, Veszprém and Zala counties – used in order to achieve their regional development objectives in the first half of the 1990s. The author measures regional development with the investment and accumulation activity of the local governments. After the Budapest agglomeration, this is the region where the concentration of inward investments is the most intensive. The examined four counties are home to one-sixth of the countryside population of Hungary, at the same time more than one-fifth of all national investments addressed this region between 1991 and 1994. Looking at the local governments only, this concentration is slightly less expressed (19%). During the four years, approximately 60 billion HUF of local government investment was carried out from many different resources: Own resources, divided revenues, central supports, acquisition of financial means and credit. On the whole, the resources listed above could provide investments worth 75-80 billion HUF. As the system of normative grants does not totally cover the costs of the obligatory responsibilities, approximately one-third of the resources which we though could be freely mobilised among the different purposes was consumed by running expenses. The actual amount of investments by the local governments in the past four years amounted to 63 billion HUF, supplemented by more than 20 billion HUF central government support. This is an average of 33,5% rate of support, slightly over (32,1%) the countryside average. Another 10-15% of the necessary resources came from within the State organisation (central organs, other local governments) and from the outside (businesses, households). Three-quarters of the remaining 52-58% share can be considered as own resources, one-fifth as credits. The counties of Nortwest Transdanubia can be divided into two sub-groups: a group with an active and another one with a moderate investment policy. The belonging to either group is mainly determined by the level of own and other mobile resources which can potentially be spent on development. Where the generation of these incomes is above the average, the county governments have better chances when joining in the competition for the resources that are available through applications. In the Northwest Transdanubian region it is Gy őr-Moson-Sopron and Veszprém which represent this type. This group is not totally homogeneous, either, as the level of the financing from credits considerably varies across the two counties. This comes from the more intensive dependence of the "free" resources on running expenses. In Veszprém county this dependence is slightly increased by the debts from the beginning of the period, which are slightly higher than the average. The two counties in the group with moderate investment activity differ from each other in important features, too. In this group too it is the final credit demand of the developments that shows significant differences. The structure of the development resources of Zala resembles that of Veszprém county. As the local government of the county adjusted their development objectives to the actual capacity of their free resources, their average demand for credit in their developments is closer to the average of the local governments of Veszprém county, too. Vas county, as a result of its income conditions weaker than the average of the region, could only have a more moderate share from the state supports which required a certain amount of own resources as well. Because of the dependence of the free resources on the running expenses, however, even these smaller scale development objectives – which nevertheless exceeded the average of the countryside – could only be provided with a level of credits significantly higher than the average.